2013
DOI: 10.1103/physrevb.87.155126
|View full text |Cite
|
Sign up to set email alerts
|

Dirac cone shift of a passivated topological Bi2Se3interface state

Abstract: Gated terahertz cyclotron resonance measurements on epitaxial Bi2Se3 thin films capped with In2Se3 enable the first spectroscopic characterization of a single topological interface state from the vicinity of the Dirac point to above the conduction band edge. A precipitous drop in the scattering rate with Fermi energy is observed that is interpreted as the surface state decoupling from bulk states and evidence of a shift of the Dirac point towards mid-gap. Near the Dirac point, potential fluctuations of 50 meV … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 46 publications
3
35
0
Order By: Relevance
“…[9][10][11][12][13][14][15] High quality epitaxially grown thin films of Bi 2 Se 3 have relatively low n-type bulk doping, 16 and subsequent capping with In 2 Se 3 further lowers the Fermi level of the surface states allowing conventional gating to reach the Dirac point. 8 No previous optical probe has been reported that attempts to measure the quantized Hall effect on a topological insulator as a function of gate voltage. 8,9,[17][18][19][20][21][22] We report Faraday angle and transmission measurements performed at a fixed laser frequency of ω/2π = 0.74 THz as a function of gate voltage at discrete magnetic fields up to 8 T on two topological insulating films.…”
Section: 9mentioning
confidence: 99%
See 2 more Smart Citations
“…[9][10][11][12][13][14][15] High quality epitaxially grown thin films of Bi 2 Se 3 have relatively low n-type bulk doping, 16 and subsequent capping with In 2 Se 3 further lowers the Fermi level of the surface states allowing conventional gating to reach the Dirac point. 8 No previous optical probe has been reported that attempts to measure the quantized Hall effect on a topological insulator as a function of gate voltage. 8,9,[17][18][19][20][21][22] We report Faraday angle and transmission measurements performed at a fixed laser frequency of ω/2π = 0.74 THz as a function of gate voltage at discrete magnetic fields up to 8 T on two topological insulating films.…”
Section: 9mentioning
confidence: 99%
“…8 No previous optical probe has been reported that attempts to measure the quantized Hall effect on a topological insulator as a function of gate voltage. 8,9,[17][18][19][20][21][22] We report Faraday angle and transmission measurements performed at a fixed laser frequency of ω/2π = 0.74 THz as a function of gate voltage at discrete magnetic fields up to 8 T on two topological insulating films. These Bi 2 Se 3 thin films, 40 and 60 quintuple layers thick (1 QL ≈ 1 nm), were grown epitaxially onto 0.5 mm thick sapphire substrates and capped with 10 nm thick In 2 Se 3 layers without breaking vacuum.…”
Section: 9mentioning
confidence: 99%
See 1 more Smart Citation
“…[27,28], in density functional calculations (DFT), it was found that the K adatoms on ultrathin films of Bi 2 Se 3 induce downward band bending within 2 to 3 nm from the surface, due to charge transfer from the adatoms to the TI, which lead to a Dirac-cone state, localized slightly deep into the TI. There are now intensive experimental and theoretical efforts on studying the interface states in various 3D TI-based heterostructures that carry the signature of both topology and contact conditions [1][2][3][20][21][22][23]29,30]. Below we throw light on the role of the band-bending effect in the formation of the bound electron states at the TI/NI interface.…”
Section: Introductionmentioning
confidence: 99%
“…Generally speaking, the TI boundary states have a rather wide range of tunability of the electronic properties under various perturbations, such as structural distortions [10,11] and mechanical strains [12,13], adsorption of (magnetic and nonmagnetic) atoms and molecules on the surface [14][15][16][17], an alternation of the surface termination [18,19], engineering via capping layers and interfaces with other materials [20][21][22][23], applying an external gate voltage [20,24,25], etc., some of which are accompanied by electrostatic bending of actual bands in TIs. We only briefly annotate the interesting consequences of these perturbations for the states confined at the TI boundary (of course, our literature survey is not exhaustive).…”
Section: Introductionmentioning
confidence: 99%